2021
DOI: 10.3389/fcell.2021.633925
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging of Calciprotein Particle Clearance and Receptor Mediated Uptake: Role of Calciprotein Monomers

Abstract: BackgroundThe liver-derived plasma protein fetuin A is a systemic inhibitor of ectopic calcification. Fetuin-A stabilizes calcium phosphate mineral initially as ion clusters to form calciprotein monomers (CPM), and then as larger multimeric consolidations containing amorphous calcium phosphate (primary CPP, CPP 1) or more crystalline phases (secondary CPP, CPP 2). CPM and CPP mediate excess mineral stabilization, transport and clearance from circulation.MethodsWe injected i.v. synthetic fluorescent CPM and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 35 publications
(62 reference statements)
3
31
2
3
Order By: Relevance
“…Intravital imaging of lipid droplets and macrophages in mouse livers was performed using an inverted two-photon microscope LSM MP7 (Zeiss, Germany), as previously described [19][20][21]. Briefly, after induction of anesthesia in mice [21], bolus tail vein injections of Hoechst 33258 (nucleus marker), TMRE/Rhodamine123 (markers of lobular zonation and mitochondrial membrane potential), Bodipy (lipid marker), and/or F4/80 antibody (macrophage marker) were performed approximately 30 min before the start of recording (Table 4).…”
Section: Intravital Imagingmentioning
confidence: 99%
“…Intravital imaging of lipid droplets and macrophages in mouse livers was performed using an inverted two-photon microscope LSM MP7 (Zeiss, Germany), as previously described [19][20][21]. Briefly, after induction of anesthesia in mice [21], bolus tail vein injections of Hoechst 33258 (nucleus marker), TMRE/Rhodamine123 (markers of lobular zonation and mitochondrial membrane potential), Bodipy (lipid marker), and/or F4/80 antibody (macrophage marker) were performed approximately 30 min before the start of recording (Table 4).…”
Section: Intravital Imagingmentioning
confidence: 99%
“…Several experimental studies have demonstrated the potent cytotoxic and procalcific Ca-phosphate crystals in the absence of fetuin-A [156,157] . A decrease in systemic fetuin-A increases systemic calciprotein particles and procalcification of calciprotein particles, thus promoting vascular calcification [158][159][160][161][162] .…”
Section: Discussionmentioning
confidence: 99%
“…To visualize bile canaliculi, a bolus of the bile acid analogue cholyl-lysyl-fluorescein (CLF; #451041, Corning) was intravenously injected via a tail vein catheter approximately 15 min before the end of the recording (Vartak et al 2021 ). Image analysis was done in defined regions of interest using Zen software (Zeiss, Germany), as previously described (Ghallab et al 2021a ; Koeppert et al 2021 ). Representative video/image of at least 4 mice per condition was analyzed and presented in the result section.…”
Section: Methodsmentioning
confidence: 99%